White mold-resistant, interspecific common bean breeding Line VRW 32 derived from Phaseolus costaricensis - Singh, Shree P.; Terán Santofimio, Henry; Schwartz, Howard F.; Otto, K; Debouck, Daniel G.; Roca, W.; Lema, M (Wiley, 2013)
The interspecific breeding line VRW 32 (Reg. No. GP‐287, PI 665037) of common bean (Phaseolus vulgaris L.), which is resistant to white mold [caused by Sclerotinia sclerotiorum (Lib.) de Bary], was jointly developed at the University of Idaho Kimberly Research and Extension Center, Kimberly, ID; Colorado State University, Fort Collins, CO; and CIAT, Cali, Colombia. The Idaho Agricultural Experiment Station released VRW 32 on 7 Dec. 2011. VRW 32 is the first white mold–resistant interspecific breeding line derived from P. costaricensis Freytag & Debouck, a member of the secondary gene pool of common bean. VRW 32 was derived from recurrent backcrossing between the small‐seeded (100‐seed weight < 25 g) tropical black common bean cultivar ICA Pijao and the small‐seeded wild P. costaricensis germplasm accession G 40604 (100‐seed weight < 19 g). ICA Pijao has an indeterminate upright growth habit Type II, purple flowers, and resistance to Bean common mosaic virus and tolerance to Bean golden mosaic virus. G 40604 has an indeterminate climbing growth habit Type IV and deep reddish‐purple magenta flowers. VRW 32 has growth habit Type II, white flowers, grayish‐brown seed, and white mold resistance with a score of 2.7 in the field and 4.3 in the greenhouse in Idaho and 5.5 in the greenhouse in Colorado compared with 5.7, 5.8, and 6.6, respectively, for the recurrent parent, ICA Pijao. VRW 32 matures in approximately 100 d in southern Idaho. VRW 32 may be used to study the interaction between the pathogen and different sources of white mold resistance and for pyramiding resistance from across Phaseolus spp. and introgressing higher levels of resistance into common bean cultivars.